If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2x + -9 = -10 Reorder the terms: -9 + x + -2x = -10 Combine like terms: x + -2x = -1x -9 + -1x = -10 Solving -9 + -1x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = -10 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = -10 + 9 -1x = -10 + 9 Combine like terms: -10 + 9 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| (2u+5)(9+u)=0 | | 4k-12=28 | | h=2+23t-16t^2 | | =9p | | 6-4r=3r-21 | | 180-x=3(90-x)+20 | | 5p+16p+24+6= | | 5x-11y=4 | | 6a^3=12a-5a-10 | | -6+2.4n=2.3-n | | 5x+2-2x+5= | | 8+5f=-12 | | x^2+9x+15=15 | | 7X+3X=8+X+20-1 | | 4x^2+66x-240=0 | | 1-p=-1 | | x=-25+5y | | 3x+1=15+5x | | 5x+.50y=190 | | q^2-10q-20=0 | | x^2+y^2+2x+10y-10=0 | | -(3xy-9)+3(4xy+6)= | | 33+Y=X | | 3(x-7)=23 | | 2n^3+4n^2-7=-8n-2 | | 150*t=16.1t^2+150 | | 1400x=800 | | .75(x+250)=300 | | ((2*x^3*y)-(2*y^3))dy=(3*x^5+3*x^2*y^2)dx | | X+(.15*x)=.79 | | t=16.1t^2 | | -6+2x=-5+x-3 |